Proceedings of the 16th Conference of the European Chapter of the Association for Computational Linguistics: Main Volume 2021
DOI: 10.18653/v1/2021.eacl-main.124
|View full text |Cite
|
Sign up to set email alerts
|

Civil Rephrases Of Toxic Texts With Self-Supervised Transformers

Abstract: Platforms that support online commentary, from social networks to news sites, are increasingly leveraging machine learning to assist their moderation efforts. But this process does not typically provide feedback to the author that would help them contribute according to the community guidelines. This is prohibitively time-consuming for human moderators to do, and computational approaches are still nascent. This work focuses on models that can help suggest rephrasings of toxic comments in a more civil manner. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Research has also been conducted to investigate annotation bias and annotator pools (Al Kuwatly et al, 2020;Waseem, 2016;Ross et al, 2017;Shmueli et al, 2021;Posch et al, 2018), as well as bias (especially racial) in existing datasets (Davidson et al, 2019b;Laugier et al, 2021). It was found that data can reflect and propagate annotator bias.…”
Section: Related Workmentioning
confidence: 99%
“…Research has also been conducted to investigate annotation bias and annotator pools (Al Kuwatly et al, 2020;Waseem, 2016;Ross et al, 2017;Shmueli et al, 2021;Posch et al, 2018), as well as bias (especially racial) in existing datasets (Davidson et al, 2019b;Laugier et al, 2021). It was found that data can reflect and propagate annotator bias.…”
Section: Related Workmentioning
confidence: 99%
“…A more recent work by Tran et al (2020) uses a pipeline of models: a search engine finds non-toxic sentences similar to the given toxic ones, an MLM fills the gaps that were not matched in the found sentences, and a seq2seq model edits the generated sentence to make it more fluent. Finally, Laugier et al (2021) detoxify sentences by fine-tuning T5 as a denoising autoencoder with additional cycle-consistency loss. Dathathri et al (2020) and Krause et al (2020) approach a similar problem: preventing a language model from generating toxic text.…”
Section: Related Workmentioning
confidence: 99%
“…J is computed as the average of their sentence-level product. In addition to that, we tried a similar aggregated metric GM (Pang and Gimpel, 2019;Laugier et al, 2021) which uses perplexity as the measure of fluency and employs a different aggregation method.…”
Section: Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…In controlled text generation, progress has been made in removing toxic behavior while maximizing fluency (Dathathri et al, 2019). In style transfer, the meaning of a toxic sentence is mapped onto a non-toxic target sentence (Laugier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%